Analisis Implementasi Evaluasi Formatif oleh Guru dalam Pembelajaran di Madrasah Aliyah Negeri Sumenep - Emna Laisa; Biwi Nazma Robbania; Fifi Mustaghfiroh; Musdelifah; Moh Hafifuddin (La-Tahzan: Jurnal Pendidikan Islam, 2026)
This study was motivated by the implementation of formative evaluation in the learning process at Madrasah Aliyah Negeri Sumenep as an effort to improve the quality of student-centered learning. Formative evaluation is an important part of assessment for learning because it helps teachers monitor students’ understanding continuously throughout the learning process. This study aimed to describe the planning, implementation, and follow-up of formative evaluation in learning activities at Madrasah Aliyah Negeri Sumenep. The research employed a qualitative approach with data collection techniques consisting of in-depth interviews, classroom observations, and documentation of teaching materials. Data were analyzed through data reduction, data presentation, and conclusion drawing, while validity was ensured through technique triangulation and member checking. The findings showed that teachers had implemented formative evaluation systematically through oral questioning, group discussions, short quizzes, assignments, and observation of students’ activities. The evaluation results were utilized as learning feedback to improve instructional strategies, conduct remedial and enrichment activities, and increase student engagement in the learning process. Although several obstacles were identified, including limited instructional time, large class sizes, and diverse student characteristics, formative evaluation proved to contribute positively to learning effectiveness and students’ understanding. The findings indicate that formative evaluation supports adaptive, responsive, and student-centered learning in the context of madrasah aliyah education.